Self-assembly between dicarboxylate ions and dinuclear lanthanide complexes: A surprisingly complicated problem - Sørensen, T; Hill, L; Tilney, J; Blackburn, O; Jones, M; Tropiano, M; Faulkner, S (Wiley, 2014)
The association between dinuclear lanthanide complexes and dicarboxylate guests has been studied to elucidate the factors that influence the self-assembly of these ternary structures. The self-assembly between α,α-bis(Eu·DO3A)-m-xylyl (H3DO3A = 1,4,7,10-tetraazacyclododecane-1,4,7-triacetic acid) host complexes and dicarboxylate guests and the association of a dinicotinate guest and an α,α-bis(Ln·DO3A)-3,5-dimethylpyridine host in water were demonstrated, and the study of lanthanide-mediated self-assembly and the methods used to investigate the self-assembly are discussed in detail. Furthermore, the self-assembly has been extended to involve five ions from across the lanthanide series, namely, Nd3+, Eu3+, Tb3+, Dy 3+ and Yb3+. The self-assembly process, measured by the association constant Ka, is independent of the nature of the lanthanide centre but it is highly solvent dependent. The association constants between a given host-guest pair vary by several orders of magnitude when determined in methanol, methanol/water and water. We conclude that although a lanthanide-centred self-assembly process can be controlled through design, the strength of the association can only be rationalised after the event. The multiple parameters involved in the determination of the value of the association constant appear to be dominated by the solvation contribution to a degree that specific and general solvation has to be understood before we can fully rationalise the association between dinuclear lanthanide complexes and dicarboxylate guests. The forces that control the self-assembly between dicarboxylate guests and dinuclear lanthanide complexes are explored and are more complicated than anticipated. Copyright © 2014 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.